Pengembangan Aplikasi Pembelajaran Mobile Learning Dengan Ispring Suite Pada Mata Kuliah Penilaian Hasil Belajar - Debora Debora; Marko Ayaki Lumbantobing (FKIP Universitas Palangka Raya, 2021)
The use of E-Learning applications is currently very much needed in overcoming gaps in face-to-face lectures along with technological developments and learning gaps during the pandemic. This study aims to develop an Android-based ISpring Suite 8.0 learning application for Mechanical Engineering Education Students as one of the E-Learning facilities in the Learning Outcomes Assessment course. In addition, this study aims to determine the feasibility of applications and student perceptions of the applications being developed. This study uses research and development methods. The results of the feasibility test data for the learning application from media experts can be obtained by a percentage of the feasibility of 91.4% in the very feasible category, for the results from material experts of 76.9% in the feasible category, for the results of the respondent's assessment of the product trial by 86% in the category. very feasible, and the results of the respondents' assessment on the usage test were 83.8% in the very feasible category. In addition, students' perceptions and expectations of the Mobile Learning application in the Mechanical Engineering Education Study Program amounted to 80%. Based on the criteria of Steer (1993), thus, the level of satisfaction is between (80% - 100%) which means high satisfaction, so the quality of the Mobile Learning application is perceived by users to achieve high satisfaction.